Promocja monografii poświęconej twórczości Anny Frajlich w Krakowie - Pasterski, Janusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
This article presents report from the meeting promoting the monograph „Tu jestem / zamieszkuję własne życie”. Studia i szkice o twórczości Anny Frajlich edited by Wojciech Ligęza and Jolanta Pasterska. The book promotion meeting was organized by Biblioteka Kraków in the Journalist Club „Pod Gruszką” in Kraków on March 23, 2018. The special guest of the event was the poet Anna Frajlich.
Promotion of a monograph dedicated to the work of Anna Frajlich in Kraków
Keywords: Anna Frajlich; monografia; poezja współczesna; promocja; monograph; modern poetry; book promotion meeting